Cerebral Asymmetry in Insomnia Sufferers - St-Jean, Genevieve; Turcotte, Isabelle; Bastien, Célyne H. (Frontiers in Neurology, 2012)
Cerebral asymmetry is used to describe the differences in electroencephalographic activity between regions of the brain. The objective of this study was to document frontal, central and parietal asymmetry in psychophysiological (Psy-I) and paradoxical (Para-I) insomnia sufferers as well as good sleepers (GS), and to compare their patterns of asymmetry to others already found in anxiety and depression. Additionally, asymmetry variations between nights were assessed. Participants were 17 Psy-I, 14 Para-I and 19 GS (mean age=40 years, SD=9.4). They completed three nights of polysomnography recordings following a clinical evaluation in a sleep laboratory. All sleep cycles of Nights 2 and 3 were retained for power spectral analysis. The absolute activity in frequency bands (0.00 to 125.00Hz) was computed at multiple frontal, central and parietal sites in REM and NREM sleep to provide cerebral asymmetry measures. Mixed model ANOVAs were computed to assess differences between groups and nights. Correlations were performed with asymmetry and symptoms of depression and anxiety from self-reported questionnaires. Over the course of the two nights, Para-I tended to present hypoactivation of their left frontal region but hyperactivation of their right one compared with GS. As for Psy-I, they presented increased activation of their right parietal region compared with Para-I. Asymmetry at frontal, central and parietal region differed between nights. On a more disrupted night of sleep, Psy-I had increased activity in their right parietal region while Para-I presented a decrease in cerebral activity in the right central region on their less disrupted night of sleep. Anxious and depressive symptoms did not correlate with asymmetry at any region. Therefore, Psy-I and Para-I present unique patterns of cerebral asymmetry that do not relate to depression or anxiety, and asymmetry varies between nights, maybe as a consequence of variability in objective sleep quality from night to night.